Evaluation of the Nigerian Beverage Industry’s Total Quality Management - Abiola, Oluranti; Obi, Ikechukwu; Ogedengbe, Temitayo; Oke, Adekola (Journal of Engineering Science and Technology Management, 2025)
This study examines the implementation and effectiveness of Total Quality Management (TQM) practices within Nigeria’s beverage industry, focusing on eight critical factors: management leadership, quality department, training, product/service design, supplier quality management, process management, quality data and reporting, and employee relations. Data were collected from 92 respondents across five leading beverage companies using a validated questionnaire based on Black and Porter’s (2007) TQM framework. Descriptive analysis using IBM SPSS Statistics Grad Pack revealed that the overall level of TQM practice in the industry is moderate. Strengths were identified in the visibility and coordination of the quality department, process automation, and top management’s commitment to training. However, significant gaps exist in supplier quality management, availability and utilization of quality data, and employee involvement in quality decisions. The findings indicate that while foundational TQM elements are in place, strategic areas critical for achieving comprehensive quality excellence remain underdeveloped. The study underscores the importance of closing performance gaps through better supplier integration, data-driven decision-making, and enhanced employee feedback mechanisms. This research contributes to the understanding of TQM implementation challenges in emerging markets and provides practical insights for improving quality performance in Nigeria’s beverage sector.